Industry (UAPASTF) Response to Pesticide Regulators’ “State of the Knowledge” Review of Drone Use for Pesticide Application: Best Practices for Safe and Effective Application of Pesticides - Hector Portillo; Roberto Barbosa; Matt Beckwith; Tyler Gullen; Rebecca Haynie; Sarah Hovinga; Banugopan Kesavaraju; Edward Lang; Pamela Livingston; Neill Newton; Mark Oostlander; Greg Watson; et al. (Drones)
The Organization of Economic Cooperation and Development Working Party on Pesticides (OECD WPP) Drone/UAV Subgroup published a “state of the knowledge” report on pesticide application using unmanned aerial vehicles (UAV) in 2021. One of the recommendations made in this report was to “develop and publish a user-friendly summary of best practices (including the essential nature of calibration), pitfalls and a trouble shooting guide (both for generating trials data and applying pesticides in practice)”. In response to recommendations in that report, the pesticide registrant industry in the United States formed the global Unmanned Aerial Pesticide Application System Task Force (UAPASTF). This report outlines the overview of the “Best Management Practices” (BMP) guidance that was developed by the UAPASTF. UAV-based spraying of crop protection products is relatively new for most of the regions globally. Therefore, this guidance document is intended to serve as an excellent resource for growers, researchers (both academics and industry) and other relevant stakeholders to carry out UAV-based spray application in an efficient and safe manner.